Soil Biological Health under Long-term Fertilization in Sorghum- Wheat Sequence on Swell-Shrink Soils of Central India - S.D. Jadhao, S.M. Jadhao, B.V. Saoji, P.A. Gite, A.B. Age, D.V. Mali, V.K. Kharche (Journal of the Indian Society of Soil Science, 2016)
A permanent field experiment is continuing since 1984-85 on a swell-shrink soil (Vertic Haplustept) at Research Farm, AICRP on Integrated Farming Systems Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola, (Maharashtra) with a view to study the effect of integrated nutrient management (INM) on soil fertility and productivity of sorghum-wheat crop sequence. The long-term impact of different nutrient management options on soil biological properties was studied during 2010-11 (27th crop cycle). The treatments comprised of different levels of RDF viz., 50, 75 and 100% of recommended NPK along with FYM, wheat straw, leuceana loppings and farmers’ practice. The population of bacteria (87.5×106 cfu), fungi (15.25×104 cfu) and actinomycetes (16.25×104 cfu) was significantly influenced with the application of 50% N through FYM along with 50% RDF. The INM using FYM also exerted a profound effect on microbial biomass carbon (267 mg kg-1), CO2 evolution (50.3 mg 100 g-1 soil), dehydrogenase (36.7 µg TPF g-1 d-1), urease (78.4 µg NH4-N g-1 d-1) and alkaline phosphatase activity (194 µg p-nitrophenol g-1 d-1). Similarly, green manuring with leucaena loppings and crop residue recycling using wheat straw in conjunction with fertilizers recorded significant improvement in soil biological properties over fertilizers alone. The biological properties were drastically deteriorated where no organics were used continuously for 27 years. The microbial biomass carbon showed significant and positive correlation with organic carbon (r = 0.743**), available N (r = 0.713**), available P (r = 0.773**) and available K (r = 0.717**). Also, strong correlations were observed between yield and dehydrogenase activity (r = 0.606**), available P (r = 0.588**) and available N (r = 0.524**) content of the soil.